MANUFACTURE ISOLATES PROTEIN OF CARP (Osphronemus gouramy) WITH DIFFERENT pH METHODS - Tika Oktasari; Suparmi '; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study aimed to get protein isolate carp (Osphronemus gouramy) with different pH methods. A total of carp 10,5 kg was obtained from the modern market in Pekanbaru. The metode of this research was completely randomized design (CRD). The treatment consists of (P1 = pH 9 dan pH 4, P2 = pH 9 dan pH 5, P3 = pH 10 dan pH 4, P4 = pH 10 dan pH 5, P5 = pH 11 dan pH 4, P6 = pH 11 dan pH 5). The results showed that the treatment P6 (pH 11 dan pH 5) wich is an average of 6.44 g with the amount of yield 12.88%. Where the result of proximate lamely: water content 4.17% bb, ash content 15.29% bk, fat content 1.98% bk, protein content 80.10% bk, and carbohydrates 2.63% bk, with a total amino acid content is 61.60%, wich dominates the amino acid is glutamic acid (9.49%), lysine (8.01%), and aspartic acid (7.22%).Keywords: Carp, pH, Protein Isolate